2023
DOI: 10.3390/polym15061497
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Nanofibrillar Polypropylene-Based Composite Microcellular Foams with Enhanced Mechanical and Flame-Retardant Performances

Abstract: With the increasing demand for plastic components, the development of lightweight, high strength and functionalized polypropylene (PP) from a cost-effective and environmentally friendly process is critical for resource conservation. In situ fibrillation (INF) and supercritical CO2 (scCO2) foaming technology were combined in this work to fabricate PP foams. Polyethylene terephthalate (PET) and poly(diaryloxyphosphazene)(PDPP) particles were applied to fabricate in situ fibrillated PP/PET/PDPP composite foams wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…This result is consistent with our previous works. 21,27 The immiscible nature of the PET phase and PP matrix, associated with strong elongation flow action during the INF process, are major factors influencing the formation of the fibrillar network. Additionally, the average diameter of PET fibrils in the PP/PET(F)/Talc composite is significantly reduced from 368 to 231 nm when compared with the PP/PET(F) sample.…”
Section: Inf Composite Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…This result is consistent with our previous works. 21,27 The immiscible nature of the PET phase and PP matrix, associated with strong elongation flow action during the INF process, are major factors influencing the formation of the fibrillar network. Additionally, the average diameter of PET fibrils in the PP/PET(F)/Talc composite is significantly reduced from 368 to 231 nm when compared with the PP/PET(F) sample.…”
Section: Inf Composite Morphologymentioning
confidence: 99%
“…26 In addition, during the INF process, the in situ nanofibrillar phase can improve the dispersion and enhance the reinforcing effect of micro/nanofillers. 23 Some studies have indicated that the lightweight, high-strength, and functionalized polymer foams can be fabricated by INF technology with microcellular batch foaming 22,24,27 and injection foaming with supercritical N 2 . 8,15,16,21 Nevertheless, to our best knowledge, there is almost no relevant research about the synergistic effect of the in situ fibrillar phase and fillers on the foamability of PP based on CFIM technology.…”
Section: Introductionmentioning
confidence: 99%